2010
DOI: 10.1097/inf.0b013e3181da8f23
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Hospitalizations From All-Cause Gastroenteritis in Children Younger Than 5 Years of Age in Brazil Before and After Human Rotavirus Vaccine Introduction, 1998–2007

Abstract: Rotavirus vaccination was introduced in Brazil in March 2006. We describe trends in hospitalizations from all-cause gastroenteritis in children younger than 5 years during pre- and postvaccination periods using hospital discharge data from Brazil Hospital Information System (SIH-SUS). A reduction in gastroenteritis hospitalizations of 26% and 48% in 2006 and in 2007, respectively, was observed among children younger than 1 year compared with prevaccination period (1998-2005). The largest reduction rates among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 7 publications
4
31
0
6
Order By: Relevance
“…In southern Brazil, the risk of children under one year being ill was 3.59 times higher than in children one to four years old. (6) It was observed that the risk for two-year-old children changed a little, with a small reduction in the year 2009, and that the pre-and post-vaccination periods remain virtually unchanged (Table 2) although they present a variation rate of (-25.8%).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In southern Brazil, the risk of children under one year being ill was 3.59 times higher than in children one to four years old. (6) It was observed that the risk for two-year-old children changed a little, with a small reduction in the year 2009, and that the pre-and post-vaccination periods remain virtually unchanged (Table 2) although they present a variation rate of (-25.8%).…”
Section: Discussionmentioning
confidence: 99%
“…(11) The study conducted in Brazil, in 2006 and 2007, found a 14% reduction in the hospitalization rates for acute diarrhea by region, with a mean hospitalization rate of 115.74 cases per 10,000 children before the introduction of the vaccine, 85.84 in 2006 and 59.94 in 2007 (a reduction of 25.8% and 48%, respectively). (6) Meanwhile,in the city of São Paulo, a reduction of 29% in hospitalizations for diarrhea of any cause was found after oral human rotavirus vaccine. (5) Identifying the causes of diarrhea is essential,-so that appropriate measures are instituted for its prevention.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations